PENANAMAN MINAT BELAJAR SISWA PADA SISWA KELAS 3 SDN 1 TEBLURU - Sasti, Mei; Emilia, Firla (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2024)
Interest in learning is the psychological drive from within students to learn something with full awareness, tranquility, and discipline. The purpose of this research is to describe the cultivation of students' interest in learning, thereby attracting students to engage in learning. The method used in this research is descriptive-qualitative. The sources of this research are third-grade homeroom teachers. The instruments used are interviews and observations conducted by both students and teachers. The findings of this research reveal the teacher's techniques in cultivating students' interest in learning. In conclusion, the teacher cultivates students' interest in learning by generating interesting ideas to captivate students' curiosity in the learning process.